FLOTATION SEPARATION OF SCANDIUM AND LANTHANUM OXALATE - V. F. Sazonova; M. A. Kozhemiak; E. I. Blaschuk (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
The article provides the results of studies of flotation separation of scandium and lanthanum by transforming them into oxalate complexes (oxalate) followed by flotation using cationic collector – dodecylamine chloride. The kinetics of flotation isolation of scandium and lanthanum from their binary solutions has two stages and it is described by the equation of the first order. The rate constants are in the range 0,073-0,015 min-1 (pH = 3) and 0,108-0,029 min- 1 (pH = 6). The essential role in the process of flotation separation of scandium and lanthanum oxalate are playing the stability of their complexes and complexes affinity to the collector.The maximum value of the separation (KSc, La=12,1) is observed in the case of: triply complexes М(С2О4)33- of scandium and lanthanum, slightly alkaline medium (pH = 6) and flow collectorin the quantity 150% of the stoichiometrically required for binding of scandium (as morelighter REE) as a compound of (RNH3)+3[M(С2О4)3]3-.